Observation of the single-ion magnet behavior of d8 ions on two-coordinate Co(i)–NHC complexes. Issue 12 (25th September 2015) - Meng, Yin-Shan; Mo, Zhenbo; Wang, Bing-Wu; Zhang, Yi-Quan; Deng, Liang; Gao, Song
Abstract : The first single-ion magnet (SIM) [Co(IMes)2 ][BPh4 ] (IMes: 1, 3-dimesitylimidazol-2-ylidene) with d 8 electronic configuration has been found in two-coordinate Co(i )–NHC complexes. Abstract : The slow magnetic relaxation typical for single-ion magnets has been known for certain low-coordinate 3d metal complexes with d 6, d 7, and d 9 electronic configurations, but never for d 8 complexes. Herein, we report a study on two-coordinate d 8 cobalt(i )–N-heterocyclic carbene complexes, for which slow magnetic relaxation behavior was observed for [Co(IMes)2 ][BPh4 ] (IMes: 1, 3-dimesitylimidazol-2-ylidene) under an applied dc field. The system represents the first d 8 single-ion magnet, and features a fitted energy barrier of U eff = 21.3 cm −1 and pre-exponential factor of τ 0 = 6.6 × 10 −6 s. The analog two-coordinate cobalt(i ) complexes with different NHC ligands, [Co(sIMes)2 ][BPh4 ] (sIMes: 1, 3-dimesitylimidazolin-2-ylidene) and [Co(IAd)2 ][BAr F 4 ] (IAd: 1, 3-dimesitylimidazol-2-ylidene; BAr F 4 : tetra(3, 5-ditrifluoromethylphenyl)borate), do not show such single-ion magnet behaviour. Ab initio calculations imply that the dihedral angle between the two NHC planes and the degree of unsaturation of the NHC ligands can dramatically alter the D value of the two-coordinate cobalt(i )–NHC ions, possibly via changing of the Co–NHC π-interactions, and hence affect the spin–orbit coupling splitting.